EVALUATION OF ANTIMICROBIAL ACTIVITY AND PHYTOCHEMICAL SCREENING OF EPICARP AND ENDOCARP PARTS OF ELAEOCARPUS GANITRUS - JIKASMITA DALEI; DEBASISH SAHOO (International Journal of Pharma and Bio Sciences, 2016)
In this present study, in vitro antimicrobial activity of methanol, and acetone extracts of epicarp and endocarp of Elaeocarpus ganitrus were investigated. The extracts exhibited antimicrobial activities with zones of inhibition ranging from 9.5mm to 21.0mm and 10.5mm to 22 mm for methanol and acetone extracts respectively. The minimum inhibitory concentration (MIC) of the epicarp acetone extract against different microorganisms was ranged between 0.5 to 0.8 mgml-1, while that of the endocarp acetone extract ranged between 0.6 to 1.0 mgml-1. Again all the extracts exhibited appreciable activity against the fungal species were investigated. The zones of inhibition exhibited by the extracts against the test fungal species ranged between 9 to18mm and 10 to 21 mm for methanol and acetonic extracts respectively. Phytochemical screening revealed the presence of tannin, glycosides, alkaloids, quinines, steroid, cumarins, phenols and flavonoids in the extracts. The ability of the crude epicarp and endocarp extracts of E.ganitrus to inhibit the growth of bacteria and fungi is an indication for its broad spectrum antimicrobial potential which may be employed in the management of microbial infections.